If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 15y + 10 = 0 Reorder the terms: 10 + 3x + 15y = 0 Solving 10 + 3x + 15y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + 3x + -10 + 15y = 0 + -10 Reorder the terms: 10 + -10 + 3x + 15y = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 3x + 15y = 0 + -10 3x + 15y = 0 + -10 Combine like terms: 0 + -10 = -10 3x + 15y = -10 Add '-15y' to each side of the equation. 3x + 15y + -15y = -10 + -15y Combine like terms: 15y + -15y = 0 3x + 0 = -10 + -15y 3x = -10 + -15y Divide each side by '3'. x = -3.333333333 + -5y Simplifying x = -3.333333333 + -5y
| 4y+33=7y | | x/10=1/2 | | 8r-29=-54+3r | | 7.3(3x+4)=7 | | -4(x+4)=8 | | 9/14x7/10= | | w/9-4/6 | | 3y-21=-45+9y | | b-7+4b=20 | | 8p^3=8p(p+2) | | (3-b)*0.8=1.6 | | Lg(x+4)=14 | | (3-b)*4/5=1.6 | | 3y^2-12x=0 | | 6z-6=3z+3 | | (2.7+m)*8=83.2 | | 2.5/X=12/16 | | 4+5v=24 | | 5n=12+13 | | 14*(15+x)=980 | | 8(3s+1)=56 | | 3G+1=26 | | x+0.0625x=76.75 | | 6(2l+8)=144 | | 9000/395000 | | 2(5+2x)=2(3x)+6 | | -11/8x=5/6 | | 10=8+w | | 4(a-3)=64 | | (4x+3)+2(2x+5)= | | -11y=2/3 | | -22=4y-2 |